Two Sides of the Same Rupee? Comparing Demand for Microcredit and Microsaving in a Framed Field Experiment in Rural Pakistan. (21st November 2017) - Afzal, Uzma; d'Adda, Giovanna; Fafchamps, Marcel; Quinn, Simon; Said, Farah
Abstract : We use a field experiment to test whether saving and borrowing satisfy demand for lump‐sum accumulation from regular deposits. Inspired by ROSCAs, we offer different credit and saving contracts to subjects. We find that individuals often accept both credit and saving contract across experimental waves. This behaviour can be rationalised by assuming that individuals seek lump‐sum payments and struggle to hold savings. Structural estimation of this model accounts for the behaviour of 75% of participants. Of these, two‐thirds have high demand for lump‐sum accumulation but savings difficulties. These results imply that the distinction between microlending and microsaving is largely illusory.